Patient outcomes up to 15 years after stroke: survival, disability, quality of life, cognition and mental health. Issue 10 (22nd July 2016) - Crichton, Siobhan L; Bray, Benjamin D; McKevitt, Christopher; Rudd, Anthony G; Wolfe, Charles D A
Abstract : Background: The global epidemiological shift of disease burden towards long-term conditions means understanding long-term outcomes of cardiovascular disease is increasingly important. More people are surviving stroke to experience its long-term consequences, but outcomes in people living more >10 years after stroke have not been described in detail. Methods: Data were collected for the population-based South London Stroke Register, with participants followed up annually until death. Outcomes were survival, disability, activity, cognitive impairment, quality of life, depression and anxiety. Findings: Of 2625 people having first-ever stroke, 262 (21%) survived to 15 years. By 15 years, 61% (95% CI 55% to 67%) of the survivors were male, with a median age of stroke onset of 58 years (IQR 48–66). 87% of the 15-year survivors were living at home and 33.8% (26.2% to 42.4%) had mild disability, 14.3% (9.2% to 21.4%) moderate disability and 15.0% (9.9% to 22.3%) severe disability. The prevalence of disability increased with time but 1 in 10 of the 15-year survivors had lived with moderate-severe disability since their stroke. At 15 years, the prevalence of cognitive impairment was 30.0% (19.5% to 43.1%), depression 39.1% (30.9% to 47.9%) and anxiety 34.9% (27.0% to 43.8%), and survivors reported greater loss of physical than mental quality of life. Conclusions: One in five people live at least 15 years after a stroke and poor functional, cognitive and psychological outcomes affect a substantial proportion of these long-term survivors. As the global population of individuals with cardiovascular long-term conditions grows, research and health services will need to increasingly focus on preventing and managing the long-term consequences of stroke.